Land use and transport European research towards integrated policies - Marshall, Stephen, 1967-; Banister, David (Elsevier, 2007)
This is a text/reference, written in a style accessible to non-specialists as well as academic researchers. It shows the inter-relationships between transport and land use planning, emphasising the nature of their integration, and showing benefits of integration. It demonstrates research findings and draws conclusions for application to policy and practice. It is coherent and comprehensive and is based on a major set of recently completed European research projects (PLUME). *Focuses on the relationships between transport and land use planning*Addresses.
Keywords: Land use -- Europe -- Planning.; Transportation -- Europe -- Planning.; Europe.; elektronické knihy; electronic books